PENGARUH MODEL COOPERATIVE SCRIPT DENGAN GAME ONLINE WORDWALL TERHADAP PENINGKATAN KOMUNIKASI MATEMATIS DAN MINAT BELAJAR SISWA - Hamidah, Hamidah; Fadilah, Fadilah; Kusuma, Jaka Wijaya (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2024)
This study aims to determine the effect of the Cooperative Script learning model combined with Wordwall online games on improving the mathematical communication skills and interests of junior high school students. The research was conducted quantitatively with a pretest-posttest control group design. The research sample consisted of 35 students in class VIIA and 36 students in class VIIIB who were chosen randomly. The experimental group was given learning using Cooperative Script with the Wordwall games, while the control group used the conventional methods. The instruments used include mathematical communication ability tests and student learning interest questionnaires. Interest questionnaire data were analyzed using descriptive statistics, while mathematical communication ability test data were analyzed using inferential statistics consisting of prerequisite tests, hypothesis testing, n-gain tests, and correlation tests. The results showed that students' learning interest in the experimental group experienced a higher increase compared to the control group. In addition, the use of the Cooperative Script learning model with Wordwall online games significantly improves students' mathematical communication skills compared to conventional methods. The results of the R square determination coefficient test also show that the Cooperative Script learning model with the online game Wordwall has a 60% influence on students’ mathematical communication skills.